2017
DOI: 10.1038/micronano.2017.72
|View full text |Cite
|
Sign up to set email alerts
|

CAD/CAM for scalable nanomanufacturing: A network-based system for hybrid 3D printing

Abstract: Micro- and nano-structuring have been highlighted over several decades in both science and engineering fields. In addition to continuous efforts in fabrication techniques, investigations in scalable nanomanufacturing have been pursued to achieve reduced feature size, fewer constraints in terms of materials and dimensional complexity, as well as improved process throughput. In this study, based on recent micro-/nanoscale fabrication processes, characteristics and key requirements for computer-aided design and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 91 publications
0
2
0
Order By: Relevance
“…Ahn et al also suggested a hybrid 3D printing process consisting of aerodynamically focused nanoparticle (AFN) printing, micromachining, and focused ion beam milling, and spin-coating ( Fig. 13a-i) [91][92][93]. This hybrid process showed the potential to overcome the limitations of individual techniques by enabling improved scaling, dimensional degree of freedom, and high-resolution down to ~ 50 nm.…”
Section: Opportunitiesmentioning
confidence: 99%
“…Ahn et al also suggested a hybrid 3D printing process consisting of aerodynamically focused nanoparticle (AFN) printing, micromachining, and focused ion beam milling, and spin-coating ( Fig. 13a-i) [91][92][93]. This hybrid process showed the potential to overcome the limitations of individual techniques by enabling improved scaling, dimensional degree of freedom, and high-resolution down to ~ 50 nm.…”
Section: Opportunitiesmentioning
confidence: 99%
“…We are now in the process of setting up such 3DP facilities as an intentional synergetic economy. (Gao 2016;Guo, Lv, and Bai 2019;Campbell and Ivanova 2013;Peng et al 2019;Jonušauskas et al 2019;Yoon et al 2017;Ahmad, Gopinath, and Dutta 2019;Mineta, Masuda, and Hong 2018;Berger 2009) Graphene is conducting and computing and can be printed at quantum scales lending itself to the design of graphene quantum dots. PLA provides the base substrate.…”
Section: []mentioning
confidence: 99%